2021
DOI: 10.1186/s13722-021-00276-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of electronic administration of patient reported outcomes using mHealth platform in emergency department patients with non-medical opioid use

Abstract: Background The emergency department (ED) offers an important opportunity to identify patients with opioid use disorder (OUD) and initiate treatment. However, post-ED follow-up is challenging, and novel approaches to enhance care transitions are urgently needed. Outcomes following ED visits have traditionally focused on overdose, treatment engagement, and mortality with an absence of patient reported outcomes (PROs), for example patient ability to schedule follow-up OUD treatment appointments or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Only by measuring PROs can we be confident that patients recover to their baseline, pre-emergency health status to the extent possible. Additionally, innovative PROMs-based solutions in emergency medicine could have a significant, positive impact on patients being treated for mental health issues and alcohol and substance abuse [36]. For now, research into PROMs in emergency medicine remains challenging and needs further work to achieve success.…”
Section: A Broader Perspectivementioning
confidence: 99%
“…Only by measuring PROs can we be confident that patients recover to their baseline, pre-emergency health status to the extent possible. Additionally, innovative PROMs-based solutions in emergency medicine could have a significant, positive impact on patients being treated for mental health issues and alcohol and substance abuse [36]. For now, research into PROMs in emergency medicine remains challenging and needs further work to achieve success.…”
Section: A Broader Perspectivementioning
confidence: 99%
“…A total of 14 studies met the criteria and were included in the review [9,[23][24][25][26][27][28][29][30][31][32][33][34][35]. Details of the search and stages of selection are outlined in Figure 1.…”
Section: Overviewmentioning
confidence: 99%
“…Similarly, a wearable biosensor for overdose monitoring also had a high level of support from participants and a willingness to wear it [25]. Although the study by Hawk et al [24] had a high initial survey response rate (95%), which highlights interest among opioid users, completion of the surveys declined over the course of 1 month, from 97% at baseline to 42% at 4 weeks. Kanter et al [9] found that patients were willing to wear the device to monitor opioid overdose all the time (76%).…”
Section: Usability Feasibility and Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Combining the themes of Emergency Department setting and use of technology, Hawk et al [ 7 ] look at the feasibility of using a mobile application to help track outcomes for patients started on buprenorphine in the Emergency Department. Even in an urban setting familiar themes of poor internet access, limited digital skills among patients, and intricacies associated with the application interfered with the majority of patients completing follow-up surveys, though many did complete surveys successfully.…”
mentioning
confidence: 99%